Optimizing Side Guard Angles on Multi-to-Single Conveyors to Minimize Infeed Stuck and Increase Overall Equipment Effectiveness - Lusianawati; Muchamad Malik; Wardatul Jannah (Fakultas Teknik Universitas Samudra, 2026)
Conveyor system efficiency is essential for maintaining smooth material flow in beverage manufacturing. At PT XYZ, frequent empty-can jamming (infeed stuck) in the multi-to-single conveyor section caused significant filler machine downtime and reduced production efficiency. This study investigated the effect of optimizing the side guard angle from 3° to 2° on reducing infeed stuck and improving Overall Equipment Effectiveness (OEE). Operational data were collected over five working days through direct observation, production reports, and angle measurements using a digital angle finder. Conveyor performance was evaluated using the availability, performance, and quality components of OEE. The results showed that reducing the side guard angle to 2° improved material flow by decreasing the average infeed stuck duration from 128.0 to 73.1 minutes. Product defects were reduced from 65 to 9 cans, while the production rate increased from 36,300 to 47,760 cans/h. Consequently, the OEE increased from 55.36% to 83.92%, representing an improvement of 28.56%. These findings demonstrate that optimizing the side guard angle effectively minimizes conveyor downtime and speed losses while enhancing production efficiency. The proposed adjustment provides a practical basis for standardizing conveyor setup to improve manufacturing productivity